PENILAIAN DIAGNOSTIK SEBAGAI FONDASI PEMBELAJARAN BERDIFERENSIASI - Qurrota Ayu Neina; Muhamad Burhanudin; Diyamon Prasandha; Rio Anugrah Rizkiansyah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Diagnostic assessment plays a crucial role in differentiated instruction by providing information about students' characteristics to support pedagogical decision-making. However, previous studies have generally examined diagnostic assessment and differentiated instruction separately, leaving the relationship between the two insufficiently synthesized. This study aimed to examine the role of diagnostic assessment as the foundation of differentiated instruction through a Systematic Literature Review (SLR). The review followed the PRISMA 2020 guidelines by searching articles indexed in Scopus, Web of Science, ERIC, SpringerLink, DOAJ, Emerald Insight, and Google Scholar. Of the 273 records identified, 17 empirical studies met the inclusion criteria and were analyzed using thematic synthesis, while methodological quality was assessed using the Mixed Methods Appraisal Tool (MMAT) 2018. The findings indicate that diagnostic assessment serves as the foundation of differentiated instruction by identifying students' learning readiness (88.2%), learning profiles (82.4%), and learning interests (76.5%) to inform the differentiation of content, process, and product. Although implementation remains constrained by teachers' competencies, time limitations, and institutional support, most studies reported improvements in student motivation, engagement, and learning quality. These findings confirm that diagnostic assessment functions as a pedagogical mechanism linking learner characteristics with adaptive, inclusive, and data-informed differentiated instruction. ABSTRAK Asesmen diagnostik berperan penting dalam pembelajaran berdiferensiasi karena menyediakan informasi mengenai karakteristik peserta didik sebagai dasar pengambilan keputusan pedagogis. Namun, penelitian terdahulu umumnya membahas asesmen diagnostik dan pembelajaran berdiferensiasi secara terpisah, sehingga hubungan keduanya belum tersintesis secara komprehensif. Penelitian ini bertujuan menganalisis peran asesmen diagnostik sebagai fondasi pembelajaran berdiferensiasi melalui Systematic Literature Review (SLR). Kajian dilakukan mengikuti pedoman PRISMA 2020 dengan menelusuri artikel pada Scopus, Web of Science, ERIC, SpringerLink, DOAJ, Emerald Insight, dan Google Scholar. Dari 273 artikel yang teridentifikasi, sebanyak 17 artikel empiris memenuhi kriteria inklusi dan dianalisis menggunakan sintesis tematik, sedangkan kualitas metodologis dievaluasi dengan Mixed Methods Appraisal Tool (MMAT) 2018. Hasil penelitian menunjukkan bahwa asesmen diagnostik berperan sebagai fondasi pembelajaran berdiferensiasi melalui pemetaan learning readiness (88,2%), learning profile (82,4%), dan student interest (76,5%) sebagai dasar diferensiasi konten, proses, dan produk. Meskipun implementasinya masih menghadapi kendala kompetensi guru, keterbatasan waktu, dan dukungan institusional, sebagian besar penelitian melaporkan peningkatan motivasi, keterlibatan, dan kualitas pembelajaran. Temuan ini menegaskan bahwa asesmen diagnostik merupakan mekanisme pedagogis yang menghubungkan karakteristik peserta didik dengan perancangan pembelajaran berdiferensiasi yang adaptif, inklusif, dan berbasis data.